Toxicity Study of Antidiabetics Functional Drink of Piper crocatum and Cinnamomum burmannii - MEGA SAFITHRI; SEDARNAWATI YASNI; MARIA BINTANG; ANNA SETIADI RANTI (HAYATI Journal of Biosciences, 2012)
Piper crocatum and Cinnamomum burmannii formulations is known to be a new diabetes functional drink. Thus, its toxicological profile needs to be studied. At present, the formulation was evaluated for the repeated dose toxicity study. The Sprague dawley albino rats were treated with P. crocatum and C. burmannii formulations (0, 630, 1260, and 1890 mg/kg) and administered orally for a period of 28 days in albino rats. The effects on body weight, food and water consumption, organ weight, hematology, clinical biochemistry as well as histology were studied. There were no significant differences in the body weight, organ weights and feeding habits between control and treated animals. Hematological analysis showed no marked differences in any of the parameters examined in either the control or treated groups. There were no significant changes that occurred in the blood chemistry analysis including glucose, cholesterol, triglycerides, creatinine, SGPT, and SGOT in experimental animals. Pathologically, neither gross abnormalities nor histopathological changes were observed. The formulation of P. crocatum and C. burmannii was found safe in repeated dose toxicity studies.